(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Internal displacements constitute, with in the context of forced migration, one ofthe most tragic phenomena of our time. At the same time, this “most silent phenomenon” which is always “forgotten”, occupies little space in the mass media, in political debates and in official literature and research. This article, apart from providing ageneral vision of the legal and humanitarian gaps in the protection of the IDs, alsowants to defuse and stimulate a debate considered vital to find creative solutions tothe intolerable situation that the internally displaced are exposed to.